(3JWhQ acQ GdTjYI GdEeGejI aj GdYUQGdMOjK hehba Cgd GdSfI efg (B/ s - (3CMeO eJhdi CHhQhGT CMeOs; (3MGeO WGgQ (B: s ((3GdbGgQI (B: s (3CMeO eJhdi CHhQhGT CMeO (B: s, 2014)
(3CKHJJ gPg GdOQGSI Cf GdacQ GdEeGei MOK ajg JWhQ LRFi hfSHi hbGe HgPg GdJWhQGJ BjGJ hYdeGA GdEeGejI GeKGd (B: (3BjI Gddg GdHQbYi hBjI Gddg MjOQ bdeOGQGf hYd TQjYJi hCSO Gddg NQbGfi hYHOGdhgGH fJcGHfi TQjYJ SfcdLi UGdMi fLa BHGOi GdHgHhOi hZjQge hJMOK Yf eYQaI eYfi GdTjYI dZI hEUWdGMG hHGH Yf aQb GdTjYI GdEeGejI GdbOjeI hGdMOjKI hHGH Yf eYJbOGJ GdTjYI GdEeGejI hfbOgG hHGH Yf JWhQ gPg GdeYJbOGJ hHGH Yf ehba ehba GdEeGejI hCgd GdSfg ef gPg GdJWhQGJs
(3GWQhMI (B( (3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdadSaI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdEeGeI s; (3acQ GdTjYI GdEeGejI s; (3ehba Cgd GdSfIs